Supporting the cognitive development of individuals with intellectual disabilities through a video game for emotional regulation - Marisela Hernández-Lara; Karina Caro; Ana Isabel Martínez-García (ReCIBE, 2025)
Emotional regulation is a fundamental skill for the cognitive, social, behavioral, and academic development of individuals with intellectual disabilities. However, these individuals often face significant challenges in this area. Therapeutic interventions have been designed to improve emotional regulation. Nevertheless, most interventions and studies have been directed at other populations, such as individuals with autism spectrum disorder or ADHD. Some of them have been proven to be effective in supporting individuals with intellectual disabilities, yet a promising alternative is the use of serious games, and no specific research has been found on the use of video games for the development of emotional regulation in individuals with intellectual disabilities. This article presents the first part of the design of a video game aimed at supporting the emotional regulation of individuals with intellectual disabilities, with the goal of providing an innovative and effective tool in this field.